Future touch in industry: Exploring sociotechnical imaginaries of tactile (tele)robots. (February 2022) - Barker, Ned; Jewitt, Carey
Highlights: Original concepts that strengthen paths towards a human-centred conceptualisation and imaginary of industrial futures. Critically engages with the future of the senses. Novel application of sociotechnical imaginaries to touch through a multi-sited ethnography. Abstract: This paper explores sociotechnical imaginaries for industrial robotics. It is motivated by the prospect of promoting human-centred industrial futures. Investigating the tactility of labour through a critical social perspective the research attends to the future of tactile (tele)robots and elaborates on the concepts of pedagogic, collaborative and superhuman touch. These concepts are offered as starting points to foster productive dialogues between social scientists, roboticists, environmentalists, policy makers, industrial leaders and labourers (e.g. union representatives). This paper is framed through literature and ethnographic fieldwork that contextualises and maps the dominant sociotechnical imaginaries for a future touch in industry, identifying the role of a comparative-competitive frame in sustaining a splintering of the imaginary towards utopic and dystopic extremes. Against this, the paper draws on interviews with leading roboticists to chart alternative futures where humans and robots may work together as collaborators, not competitors.